Effect of Fried Dishes Assortment on Chosen Properties of Used Plant Oils as Raw Materials for Production of Diesel Fuel Substitute - Szmigielski, Marek; Maniak, Barbara; Piekarski, Wiesław; Zając, Grzegorz (IntechOpen, 2011)
None